Brand Equity in the Drinkin' Box Market:: Canadian vs. American - Wilson, Wendy; Ouyang, Ming; Rinehart, Shelley; Grant, E. Stephen (Journal of Comparative International Management)

(untitled) (Management Futures, 2004)
Abstract Global competition forces companies to invest intensively in brands in order to hold their market positions. Hence, a company's market competitiveness can be estimated based on an assessment of its brand equity. This study developed a preliminary metric that assesses a company's brand equity based on several different dimensions. Six hundred and forty in-depth interviews were conducted to assess brand equity of the leading brand in the drinkin' box market. The assessment for the leading brand was then compared to that of other major competing brands within the New Brunswick market. Preliminary results suggest that the metric tested in this study is a valid tool for the determination of brand equity and that although the leading brand is a home brand and is able to hold its market position, competitive pressure from other brands is real and inescapable.